Silver staining of Musa chromosomes - Pillay, M.; Adeleke, M. (International Society of Cytology, 2001)
Cytological studies in Musa spp. L. are hampered by the small size and poor staining ability of the chromosomes. The aim of this experiment was to use silver nitrate as a staining agent for Musa chromosomes. The results of this study showed that silver nitrate is a useful alternative stain for cytological studies in Musa. The silver staining procedure was very effective for demonstrating the structure of prophase stages of meiosis.